Emotions and team communication in the operating room: a scoping review. Issue 1 (31st December 2023) - Lee, Henrietta; Woodward-Kron, Robyn; Merry, Alan; Weller, Jennifer
ABSTRACT: Training in healthcare team communication has largely focused on strategies to improve information transfer with less focus on interpersonal dynamics and emotional aspects of communication. The Operating Room (OR) may be one of the most emotionally charged hospital environments, and is one requiring excellent team communications. We aimed to identify literature reporting on the emotional aspects of OR team communication. Our research questions were: what are the triggers in the environment that provoke an emotional response affecting communication, and what are the emotional responses to communication between OR team members; and how do these emotional aspects of communication affect the function of the OR team? We undertook a Scoping Review of literature across relevant databases following published guidelines, and narrative synthesis of the identified studies. From the 10 included studies we identified three themes: (1) Emotional experiences in the OR and their contributors; (2) Effects of emotional experiences on team communication; and (3) Solutions to manage the emotional experiences in the OR. Theme 1 sub-themes were: (1) Range of emotions experienced in the OR; (2) Hierarchical culture and (3) Leadership expectations as contributors to negative emotions. The OR is an emotionally charged environment. The hierarchical culture can inhibit staff from speaking up, and failure of leaders to meet team expectations, e.g., through appropriate and timely communication, may cause frustration and stress. The consequences of emotions include poor team dynamics, ineffective communication and potential negative impact on patient care. Few studies described strategies to manage emotions in the OR. The studies reviewed describe an environment where emotions can run high, affecting interpersonal communications, team function and patient care. The few identified studies relevant to our research questions demonstrate a need to better understand the emotional aspects of OR team communication and the effectiveness of interventions to improve these.